(untitled) (Research, Society and Development, 2021)
Anterior crossbite refers to the abnormal vestibulolingual relationship in the sagittal dimension between one or more anterior superior and inferior anterior teeth. It can be classified as dental, functional or skeletal. Each has its own diagnostic criteria and specific treatment, and it is up to the dentist to know how to distinguish between these different natures of malocclusion. In this sense, the aim of this study is to show a case report about an ACM. Patient HCA, female, 7 years old, attending the Preventive Orthodontics Clinic of the Faculty of Dentistry of Araçatuba - UNESP, having as main complaint “untidy front tooth”. The patient has no history of systemic diseases or medication use. The patient was in the first transitional period of mixed dentition with her right maxillary central incisor in crossbite relationship with its antagonists mandibular central incisor. On both sides, the patient had the first permanent molars in Class I relationship, the deciduous second molars with mesial step and the deciduous canines in a Class I. Initially, an acrylic appliance with an expander was installed. Due to lack of cooperation, the treatment plan was changed and the patient received a fixed appliance with a 2x2 configuration, with brackets on maxillary central incisors and edgewise tubes on maxillary deciduous molars. In the lower arch, a bite lift was performed on the occlusal surface of mandibular deciduous molars to unblock the occlusion and facilitate the movement of right maxillary central incisor. The total treatment time was 60 days.